DISPERSION PATTERN OF Helopeltis antonii Signoret (HEMIPTERA:MIRIDAE) ON CASHEW PLANTATION - SISWANTO SISWANTO; RITA MUHAMAD; DZOLKHIFLI OMAR; ELNA KARMAWATI (Jurnal Penelitian Tanaman Industri, 2008)
ABSTRACTHelopeltis antonii is one of the major pests in most cashew growingareas in Indonesia. The pest attacks cashew plants in the nursery and alsoin the fields which caused significant damage. Apart of cashew the insectshave a lot of alternate host plants such as tea, cocoa, neem, pepper,mangoes, jamboes, etc. This research was aimed at investigating thedispersion pattern of H. antonii in cashew plantation. The research wasconducted in smallholder cashew plantation in Ngadirejo, Wonogiri,Indonesia from March 2004 to May 2006. The observation of H. antoniipopulation was carried out on 60 sample plants which selectedsystematically in about 2 ha cashew plantation area every two weeks.Distribution analysis using various indices of dispersion and regressionmodels was applied to evaluate the dispersion of H. antonii in cashewplantation. The result shows that variance to mean ratio (s 2 / x ), χ2, Lloydmean crowding, Green’s coefficient of dispersion and Taylor’s power lawindicate aggregated distribution when the population is high duringflushing-flowering seasons of cashew plants, and it indicates regular orrandom distribution when the population is low during post-floweringseasons. The aggregated distribution on cashew plants indicated that thereis a preferency to food sources of the plants and an individual behaviour toaggregate. Therefore, sampling and monitoring H. antonii in cashewplantation should be carried out systematically during flushing-floweringseasonsKey words: Cashew,  Anacardium  occidentale,  pest  management,Helopeltis antonii, dispersion, Central JavaABSTRAKPola sebaran Helopeltis antonii Signoret (Hemiptera:Miridae) pada pertanaman jambu meteHelopeltis antonii merupakan salah satu hama utama tanamanjambu mete yang ditemukan hampir di setiap area pengembangan mete diIndonesia. Hama ini menyerang tanaman jambu mete sejak pembibitanhingga di lapangan dengan kerusakan yang cukup signifikan. Selain jambumete, serangga ini juga mempunyai banyak inang alternatif antara lain teh,kakao, mimba, lada,mangga, jambu air dll. Penelitian ini bertujuan untukmenentukan sebaran serangga tersebut, khususnya sebaran horizontal padapertanaman jambu mete. Penelitian dilakukan di pertanaman jambu metemilik petani di daerah Ngadirejo, Wonogiri, Indonesia dari Maret 2004sampai Mei 2006. Pengamatan populasi H. antonii dilakukan pada 60tanaman sampel yang dipilih secara sistematik pada area pertanamanjambu mete seluas kurang lebih 2 ha setiap 2 minggu sekali. Hasil analisismenggunakan beberapa indek pengelompokan dan model regresi yaiturasio keragaman terhadap rata-rata (s 2 / x ), χ2,rata-rata pengelompokandari Lloyd, koefisien sebaran dari Green dan hukum kekuatan Taylormenunjukkan penyebaran yang mengelompok jika populasi tinggi selamamusim pembentukan tunas dan pembungaan jambu mete, dan merata atauacak jika populasi rendah sesudah musim pembungaan. Pengelompokan H.antonii pada tanaman jambu mete menunjukkan adanya ketertarikan padaketersediaan makanan pada tanaman jambu mete dan perilaku individuserangga tersebut. Oleh karena itu untuk pengambilan sampel danpengamatan serangga tersebut sebaiknya dilakukan secara sistematis padasaat musim pembentukan tunas dan pembungaan.Kata kunci: Jambu mete, Anacardium occidentale, pengendalian hama,Helopeltis antonii, sebaran, Jawa Tengah